Eco-innovation, a Business Approach towards Sustainable Processes, Products and Services. (2018) - Szilagyi, Aida; Mocan, Marian; Verniquet, Anne; Churican, Andrei; Rochat, David
Abstract: Eco-innovation has been wildly accepted as a method for improving the environmental performance of enterprises and for supporting them to improve their products; as well as to advance to more sustainable business models, and as a driver of business success and competitive advantage at the firm level. Implementing eco-innovation is a challenging process and will not be suitable for all organizations. Therefore understating barriers and drivers at the national and business level, as well as the main gaps in policy and education, could build a better picture of the necessary framework conditions for eco-innovation to be created in Romania. The paper reflects on existing opportunities in the country and demonstrates that eco-innovation potential needs to be addressed. Our research identified existing premises and drivers for eco-innovation that could boost the application of eco-innovation in companies, entail policy changes, and boost cooperation between stakeholders from R&D, academia, businesses, clusters and policy makers. The success of eco-innovation depends on the awareness that will be created among businesses through dissemination of strong business cases, the adjustment of the policy framework that should stimulate and reward the market for eco-innovative solutions and the capacity of experts to convince the companies' management of the financial and environmental benefits of eco-innovation, to explain the need for continuous application of eco-innovative strategies and how they can be mainstreamed in the overall enterprise strategy and overall management. Through its objectives, the ECO Partner project contributes to install a model of cooperation between main actors interested din eco-innovation and build cooperation between the main stakeholders by initiating the Romanian Eco-Innovation Network (RE-IN). The role of the RE-IN is to develop and strength the partnership and to become the main partner in Romania for policy makers, businesses, academia and experts with common interests in eco-innovation.